Serosurvey of Trypanosoma cruzi in persons experiencing homelessness and shelter workers of Brazil - Kmetiuk, Louise Bach; Gonçalves, Gustavo; Chechia Do Couto, Anahi; Biondo, Alexander Welker; Figueiredo, Fabiano Borges (Frontiers in Public Health, 2023)
Despite Chagas disease, caused by Trypanosoma cruzi, has been associated to social vulnerability worldwide producing disability and mortality, no study to date has assessed this protozoal infection in persons experiencing homelessness. Accordingly, the present study aimed to assess anti-T. cruzi antibodies by Wiener Chagatest ELISA recombinant v.3.0 in serum samples of persons experiencing homelessness and related shelter workers in São Paulo, city with reported vectors but no recent autochthonous case report. In overall, seropositivity to T. cruzi resulted in 3/203 (1.5%) persons experiencing homelessness and 2/87 (2.3%) shelter workers, with similar seroprevalence likely associated to their past social vulnerability. Although the herein seropositivity in persons experiencing homelessness and shelter workers were within the 0% to 25.1% seroprevalence for chronic Chagas disease in the general Brazilian population, disease overall has almost two-fold decreased from 1980s to 2000 and such wide range may not reflect the local disease status. In addition, the authors hypothesized that the similar seroprevalence and exposure between homeless persons and shelter workers herein may be more associated to shared past and present low-income social vulnerability than migratory movements, which may also include infection by sharing injecting drugs, vertical transmission, or blood transfusion. Thus, future studies are needed to confirm the active transmission of Chagas Diseases in São Paulo city. Moreover, Chagas disease should be always considered as differential diagnosis in homeless persons and shelter workers, even in major disease-free Brazilian or other worldwide cities, mostly due to early exposure and vulnerable living conditions.